2016
DOI: 10.1017/s0007114516001768
|View full text |Cite
|
Sign up to set email alerts
|

Calcium intake and breast cancer risk: meta-analysis of prospective cohort studies

Abstract: Findings from observational studies have suggested a possible relation between Ca and breast cancer risk. However, the results of these studies are inconclusive, and the dose-response relationship between Ca intake and risk of breast cancer remains to be determined. A meta-analysis of prospective studies was conducted to address these issues. PubMed and Embase databases were searched for relevant studies concerning the association between Ca intake and breast cancer up to March 2016. The summary relative risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…calcium chloride, calcium sulfate), and calcium may serve as a potential regulator in breast cancer cell proliferation [52]. A meta-analysis of eleven prospective cohort studies suggest an inverse dose-response association between calcium intake and breast cancer risk [53].…”
Section: Discussionmentioning
confidence: 99%
“…calcium chloride, calcium sulfate), and calcium may serve as a potential regulator in breast cancer cell proliferation [52]. A meta-analysis of eleven prospective cohort studies suggest an inverse dose-response association between calcium intake and breast cancer risk [53].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the association between dietary calcium intake and various cancer risks. Previous meta-analyses have found that dietary calcium intake might have a protective effect on colorectal cancer (RR = 0.86, 95% CI = 0.78–0.95) [44] and breast cancer (RR = 0.92, 95% CI = 0.85–0.99) [45], but have an opposite influence on the risk of prostate cancer (RR = 1.18, 95% CI = 1.08–1.30) [46], while having no significant relationship with the risk of lung cancer (RR = 0.85, 95% CI = 0.63–1.13) [47]. The findings presented in this meta-analysis add new information regarding the association between calcium intake and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse dose–‐response association between calcium intake and breast cancer risk was described. A large meta‐analysis of eleven prospective studies showed that the overall risk reduction in breast cancer for high versus low intake of calcium was 0.92 (95% CI 0.85, 0.99) . Two recent meta‐analysis of prospective studies showed that overall vitamin D blood levels are associated with reduced breast cancer risk .…”
Section: Introductionmentioning
confidence: 99%